2021
DOI: 10.1093/narcan/zcab018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IDH1/2 mutant cancers with combinations of ATR and PARP inhibitors

Abstract: Mutations in the isocitrate dehydrogenase-1 and -2 (IDH1/2) genes were first identified in glioma and acute myeloid leukemia (AML), and subsequently found in multiple other tumor types. These neomorphic mutations convert the normal product of enzyme, α-ketoglutarate (αKG), to the oncometabolite 2-hydroxyglutarate (2HG). Our group recently demonstrated that 2HG suppresses the high-fidelity homologous recombination (HR) DNA repair pathway, resulting in a state referred to as ‘BRCAness’, which confers exquisite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Here, we confirmed the presence of γH2AX after the ATRi monotherapy, PARPi:ATRi and PARPi:CHK1i combined therapy in PEO-1 cells. Our findings are consistent with previous studies [ 53 , 63 ]. Furthermore, consistent with a study by Huntoon et al, we found that γH2AX levels were increased after ATRi and CHK1i treatment alone or in combination with PARPi in BRCA MUT and BRCA WT cells [ 64 ].…”
Section: Discussionsupporting
confidence: 94%
“…Here, we confirmed the presence of γH2AX after the ATRi monotherapy, PARPi:ATRi and PARPi:CHK1i combined therapy in PEO-1 cells. Our findings are consistent with previous studies [ 53 , 63 ]. Furthermore, consistent with a study by Huntoon et al, we found that γH2AX levels were increased after ATRi and CHK1i treatment alone or in combination with PARPi in BRCA MUT and BRCA WT cells [ 64 ].…”
Section: Discussionsupporting
confidence: 94%
“…It could be interesting to mechanistically understand the role of MMR and ATR in PARP signaling by treating with PARP inhibitors and ATR inhibitors. Recently published work from our laboratory showed that PARP and ATR inhibitors synergize in the common glioblastoma mutation in isocitrate dehydrogenase 1/2 (IDH1/2), so perhaps MMR-deficiencies may also benefit from this combination 43 . Ongoing work in our laboratory continues to investigate the role of these various therapeutics in combination with ATR inhibitors in MMR-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as per preliminary findings, olaparib has been found to be safe as well as effective in IDH1/2-mutant mesenchymal sarcoma condition ( Eder et al, 2021 ). Another in vitro research has evaluated the effect of PARP inhibitors in combination with ATR inhibiting molecules in IDH1/2-mutant cells and suggested that this combination therapy elevates the premature mitotic entry in the presence of IDH1/2 mutations ( Sule et al, 2021 ). Various clinical studies are still ongoing in different phases in which PARP inhibitors are used in IDH mutated glioma patients.…”
Section: Role Of Poly (Adp-ribose) Polymerase Inhibitors In Temozolom...mentioning
confidence: 99%